Lamination method and detection method for photovoltaic tile with double-glass structure
By using two lamination chambers for segmented lamination and anti-overpressure frames during lamination of double-glass structured photovoltaic shingles, combined with buffer pads, the bubbles and glass of ultra-thick double-glass structured photovoltaic shingles are solved during lamination of ultra-thick double-glass structured photovoltaic shingles. The problem of misalignment improves production efficiency and pass rate, and ensures the film thickness and qualification of the product through testing methods.
Patent Information
- Application Number
- CN202411333504.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
When making ultra-thick double-glass structured photovoltaic shingles in the prior art, bubbles, glass misalignment, edge delamination and other problems are prone to occur during the lamination process, resulting in low pass rate and high cost.
Two lamination chambers are used for segmented lamination, combining anti-overpressure frames and buffer pads to control lamination rate and pressure gradients, avoid glass misalignment and bubble generation, and shorten production cycles and improve product qualification rates through dual-cavity layering. .
It improves the production efficiency and pass rate of double-glass structured photovoltaic shingles, reduces costs, is suitable for the manufacturing of ultra-thick double-glass structured photovoltaic shingles, and ensures the film thickness and product qualification through testing methods.
Smart Images

Figure CN119208419A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photovoltaic tiles, and in particular relates to a lamination method and a detection method for double-glass structure photovoltaic tiles. Background Art
[0002] Currently, most photovoltaic tiles are made of double glass (3.2+3.2mm, 3.2+2mm, 2+2mm) combined with PVB film lamination; the existing lamination process mostly uses double-sided heating laminators or single-layer heating laminators + autoclaves.
[0003] When ultra-thick double-glass structure photovoltaic tiles (5+4mm, 4+4mm) are produced using the existing lamination process, due to the thick front glass, irregular concave and convex embossing, and heavy weight, problems such as bubbles, glass misalignment, and edge delamination may occur during the lamination process, resulting in a low lamination pass rate for the double-glass structure photovoltaic tiles.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] In order to solve the technical problems existing in the prior art, the present invention provides a double-glass structure photovoltaic tile lamination method and a detection method. The present invention uses two lamination cavities for lamination to improve the production efficiency of the double-glass structure photovoltaic tiles. The segmented lamination method used in the lamination process can prevent the lamination rate from being too fast, and has the effect of preventing the back contact battery from shifting. At the same time, with the anti-overpressure frame, the glass misalignment during the lamination process can be avoided, thereby improving the qualified rate of the double-glass structure photovoltaic tile lamination and reducing the cost; it can be applicable to the manufacture of ultra-thick double-glass structure photovoltaic tiles.
[0006] The present invention includes the following technical solutions:
[0007] The first aspect of the present invention provides a double-glass structure photovoltaic tile lamination method, wherein a first laminated component is sequentially laminated through a first lamination cavity and a second lamination cavity of a lamination device to obtain a double-glass structure photovoltaic tile, and the first laminated component is arranged in an overpressure prevention frame for lamination;
[0008] The first lamination chamber is configured as follows: vacuuming for a first preset time, and the first lamination plate in the first lamination chamber performs segmented pressurization lamination on the first to-be-laminated component at a first preset temperature;
[0009] The second lamination chamber is configured as follows: vacuuming is performed according to a second preset time, and the second lamination plate in the second lamination chamber performs segmented pressurization and lamination on the first component to be laminated according to a second preset temperature.
[0010] Furthermore, the anti-overpressure frame has expansion and contraction in the X direction, and / or the anti-overpressure frame has expansion and contraction in the Y direction.
[0011] Furthermore, the anti-overpressure frame includes an L-shaped side, a long side and a short side, both ends of the long side and the short side are provided with connecting holes, both ends of the L-shaped side are provided with connecting parts for connecting to the connecting holes, the two long sides are symmetrically arranged in parallel, the two short sides are symmetrically arranged in parallel, and the long side is perpendicular to the short side, and the long side and the short side are connected to form a rectangle through the L-shaped side; the extension and retraction are achieved by sliding the connecting part in the connecting hole and fixed by bolts.
[0012] Furthermore, the outer diameter of the connecting portion is matched with the inner diameter of the connecting hole.
[0013] Furthermore, the first laminating board performs three-stage lamination on the first piece to be laminated, and the pressure values of the first stage lamination, the second stage lamination and the third stage lamination are increased successively; the first stage lamination, the second stage lamination and the third stage lamination are performed on the first piece to be laminated successively.
[0014] Furthermore, the second laminating plate performs three-stage lamination on the first piece to be laminated, and the pressure values of the fourth, fifth and sixth stages of lamination increase successively; the first piece to be laminated is performed with the fourth, fifth and sixth stages of lamination successively.
[0015] Furthermore, the first laminated component includes a front plate glass, a front encapsulation film, a back contact cell, a rear encapsulation film and a rear plate glass arranged in sequence from top to bottom; and the surface of the front plate glass is provided with textures.
[0016] Furthermore, the laminating surfaces of the first laminate and the second laminate are both provided with buffer pads.
[0017] Furthermore, the front packaging film is a transparent co-extruded EPE material, and the rear packaging film includes a transparent co-extruded EPE material and a black EVA material.
[0018] The second aspect of the present invention provides a method for testing the thickness of a double-glass photovoltaic tile adhesive film, comprising the above-mentioned double-glass photovoltaic tile lamination method,
[0019] The test piece is obtained by laminating a second piece to be laminated by the photovoltaic tile lamination method, wherein the second piece to be laminated includes a front plate glass, an ETFE film, a front encapsulation film, a back contact cell, a rear encapsulation film, an ETFE film and a rear plate glass arranged in sequence from top to bottom;
[0020] The front packaging film and the rear packaging film of the test piece are taken out to obtain a cross-linked combination after hot-melt cross-linking; the cross-linked combination includes an ETFE film, a front packaging film, a back contact battery, a rear packaging film and an ETFE film;
[0021] The thickness of the four corners and the middle of the long and short sides of the cross-linked combination is measured respectively, and the average thickness is obtained by the thickness calculation;
[0022] The thickness average is compared to the theoretical value for the cross-linked combination.
[0023] By adopting the above technical solution, the present invention has the following advantages:
[0024] 1. The present invention uses two lamination chambers for lamination to improve the production efficiency of double-glass photovoltaic tiles. The segmented lamination method used in the lamination process can prevent the lamination rate from being too fast, and prevent the back contact battery from shifting. At the same time, with the anti-overpressure frame, it can avoid glass dislocation during the lamination process, thereby improving the qualified rate of double-glass photovoltaic tile lamination and reducing costs; it can be applied to the manufacture of ultra-thick double-glass photovoltaic tiles.
[0025] 2. The present invention shortens the production cycle by double-cavity lamination; at the same time, by controlling the process parameters of double-cavity lamination, the product qualification rate is improved and the cost is reduced.
[0026] 3. The present invention improves the overall uniformity of heat conduction of embossed glass by combining double-cavity lamination with a lamination buffer pad. The interior of the laminate can evenly absorb the same amount of heat in a shorter time, reducing the lamination time and thus shortening the entire production cycle. At the same time, by controlling the process parameters of double-cavity lamination, the product qualification rate is improved and the cost is reduced.
[0027] 4. In the present invention, the first laminating board performs three-stage lamination on the first piece to be laminated, and the pressure values of the first lamination, the second lamination and the third lamination increase successively; the first lamination, the second lamination and the third lamination are performed on the first piece to be laminated successively; through such a step-by-step pressurization process, the pressure change rate on the surface of the first piece to be laminated is relatively lower, the pressure change amplitude per unit time is small, and the two layers of photovoltaic glass are not prone to relative displacement and misalignment, and it can also effectively avoid the displacement of the internal back contact battery caused by the local rapid flow of the molten film due to the excessive pressurization rate. At the same time, due to the segmented pressurization, the pressure received on the surface of the first piece to be laminated increases slowly and gradually, leaving more sufficient time for the air to be discharged, thereby increasing the efficiency and effect of bubble discharge in the piece to be laminated, and avoiding the poor appearance caused by the inability to discharge bubbles due to excessive pressure between the two layers of glass due to the excessive lamination rate.
[0028] 5. In the present invention, the second laminating board performs three-stage lamination on the first laminated member, and the pressure values of the fourth, fifth and sixth stages of lamination increase successively; the first laminated member is sequentially subjected to the fourth, fifth and sixth stages of lamination; through such step-by-step pressurization, appropriate pressure during the pressurization process helps to provide close contact between the adhesive film and the glass, which is beneficial to the cross-linking reaction.
[0029] 6. The present invention controls the lamination process parameters of the first lamination chamber and the second lamination chamber, so that the adhesive film is only melted in the first lamination chamber to avoid the generation of bubbles and to have the function of exhaust; while the adhesive film undergoes a cross-linking reaction in the second lamination chamber to increase the degree of cross-linking; and the working time of the first lamination chamber and the second lamination chamber are consistent, which also avoids waste of equipment and improves production efficiency.
[0030] 7. The testing method of the present invention can be used to determine the pass rate, edge delamination risk and reliability of double-glass photovoltaic tiles by measuring and comparing the thickness of the adhesive film.
[0031] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a flow chart of a double-glass structure photovoltaic tile lamination method according to an embodiment of the present invention;
[0034] Figure 2 An exploded view of an overpressure protection frame in an embodiment of the present invention;
[0035] Figure 3 A schematic diagram of the structure of an overpressure protection frame in an embodiment of the present invention;
[0036] Figure 4 is a schematic cross-sectional structural diagram of a long side in an embodiment of the present invention;
[0037] Figure 5 is a schematic cross-sectional structural diagram of a connecting portion in an embodiment of the present invention;
[0038] Figure 6 This is a schematic diagram of the structure of a double-glass photovoltaic tile in an embodiment of the present invention;
[0039] Figure 7 Schematic diagram of the sample structure for measuring the edge adhesive film thickness of the double-glass photovoltaic tile in an embodiment of the present invention;
[0040] In the figure: 10 - anti-overpressure frame, 11 - L-shaped edge, 111 - connection part, 12 - long side, 13 - short side, 14 - connection hole, 20 - double-glass structure photovoltaic tile, 21 - front glass, 22 - front packaging film, 23 - back contact battery, 24 - back packaging film, 241 - transparent co-extruded EPE material, 242 - black EVA material, 25 - back glass, 30 - bolt. DETAILED DESCRIPTION
[0041] The following description provides many different embodiments or examples for implementing different features of the present invention. The components and arrangements described in the following specific examples are only used to simplify the present invention and are only used as examples, not to limit the present invention.
[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] This embodiment provides a double-glass structure photovoltaic tile lamination method, such as Figure 1 As shown, the first laminated component is laminated in the first lamination cavity and the second lamination cavity of the lamination device in sequence to obtain a double-glass structure photovoltaic tile 20, and the first laminated component is arranged in the anti-overpressure frame 10 for lamination;
[0044] The first lamination chamber is configured as follows: vacuuming for a first preset time, and the first lamination plate in the first lamination chamber performs segmented pressurization lamination on the first to-be-laminated component at a first preset temperature;
[0045] The second lamination chamber is configured as follows: vacuuming is performed according to a second preset time, and the second lamination plate in the second lamination chamber performs segmented pressurization and lamination on the first component to be laminated according to a second preset temperature.
[0046] The present invention uses two lamination cavities for lamination to improve the production efficiency of the double-glass structure photovoltaic tiles 20. The segmented lamination method used in the lamination process can prevent the lamination rate from being too fast, and prevent the back contact battery from shifting. At the same time, the anti-overpressure frame 10 can be used to avoid glass misalignment during the lamination process, thereby improving the qualified rate of the double-glass structure photovoltaic tile lamination and reducing the cost; it can be suitable for the manufacture of ultra-thick double-glass structure photovoltaic tiles.
[0047] It should be noted that the segmented lamination should be understood as that the pressure applied by the first laminating plate and the second laminating plate on the parts to be laminated is varied, that is, the parts to be laminated are laminated in segments with different pressure values.
[0048] In some embodiments, Figure 2 As shown, the anti-overpressure frame 10 has expansion and contraction in the X direction, and / or the anti-overpressure frame 10 has expansion and contraction in the Y direction. The anti-overpressure frame 10 can be reused, and photovoltaic tile products of different sizes can be laminated by adjusting the position of the frame, which greatly reduces the tooling investment cost.
[0049] In some embodiments, Figure 2 As shown, the overpressure protection frame 10 includes an L-shaped side 11, a long side 12 and a short side 13, both ends of the long side 12 and the short side 13 are provided with connecting holes 14, and both ends of the L-shaped side 11 are provided with connecting parts 111 for connecting to the connecting holes 14. Figure 3 As shown, two long sides 12 are symmetrically arranged in parallel, two short sides 13 are symmetrically arranged in parallel, and the long sides 12 are perpendicular to the short sides 13. The long sides 12 and the short sides 13 are connected by the L-shaped side 11 to form a rectangle; the connection part 111 is slid in the connection hole 14 to achieve expansion and contraction, and is fixed by the bolt 30. When adjusting the size of the overpressure prevention frame 10, the L-shaped side 11 is pulled to slide in the connection hole 14 until the overpressure prevention frame 10 of the required size is obtained, and then the bolt 30 set on the long side 12 and / or the short side 13 is tightened to squeeze the connection part 111 so that the connection part 111 is fixed in the connection hole 14. It should be noted that the bolt 30 is set at the connection hole 14 of the long side 12 and / or the short side 13, and penetrates the connection hole 14 from the outside to the inside. It is best to set a plurality of bolts 30, and the plurality of bolts 30 are evenly arranged along the axial direction of the connection hole 14.
[0050] It should be noted that the structure of the anti-overpressure frame 10 is not limited to the above examples, and any structure that can achieve expansion and contraction in the X direction and / or the Y direction should be within the protection scope of the present invention.
[0051] In some embodiments, the outer diameter of the connecting portion 111 is matched with the inner diameter of the connecting hole 14 .
[0052] In some embodiments, Figure 4 As shown, the inner surface of the connecting hole 14 is provided with a concave-convex structure, such as Figure 5 As shown, the outer surface of the connecting portion 111 is provided with a concave-convex structure, and the connecting portion 111 cooperates with the connecting hole 14 through the concave-convex structure; and is locked and fixed by a bolt 30.
[0053] In some embodiments, the first laminating plate performs three-stage lamination on the first member to be laminated, and the pressure values of the first lamination stage, the second lamination stage and the third lamination stage increase successively, that is, the pressure value of the first lamination stage < the pressure value of the second lamination stage < the pressure value of the third lamination stage; the first member to be laminated is subjected to the first lamination stage, the second lamination stage and the third lamination stage successively, that is, the first member to be laminated is laminated for a period of time at the pressure value of the first lamination stage, then pressurized to the pressure value of the second lamination stage for a period of time, and finally pressurized to the pressure value of the third lamination stage for a period of time.
[0054] In some embodiments, the second laminating plate performs three-stage lamination on the first member to be laminated, and the pressure values of the fourth stage lamination, the fifth stage lamination and the sixth stage lamination increase successively, that is, the pressure value of the fourth stage lamination < the pressure value of the fifth stage lamination < the pressure value of the sixth stage lamination; the first member to be laminated is sequentially laminarized in the fourth stage, the fifth stage lamination and the sixth stage lamination, that is, the first member to be laminated is laminated for a period of time at the pressure value of the fourth stage lamination, then pressurized to the pressure value of the fifth stage lamination for a period of time, and finally pressurized to the pressure value of the sixth stage lamination for a period of time.
[0055] In some embodiments, Figure 6 As shown, the first laminated part includes a front glass 21, a front encapsulation film 22, a back contact battery 23, a rear encapsulation film 24 and a rear glass 25; the front glass 21, the front encapsulation film 22, the back contact battery 23, the rear encapsulation film 24 and the rear glass 25 are arranged in sequence from top to bottom, and the surface of the front glass 21 is provided with textures; the laminating surfaces of the first laminate and the second laminate are provided with buffer pads. During the heating and pressurizing process of the first laminated part, the buffer pad is completely matched and nested with the surface texture of the front glass 21, so that the front glass 21 is heated and stressed uniformly, avoiding the problem of uneven stress and heat conduction caused by direct contact between the front glass 21 and the heating plate, thereby reducing the lamination qualification rate. The temperature-resistant buffer pad is soft silicone or rubber. Among them, the buffer pad is a temperature-resistant buffer pad, which can withstand a temperature of ≥120°C and meet the lamination process requirements of photovoltaic modules.
[0056] Among them, the front glass 21 uses irregular deep-grained rolled low-iron high-transmittance glass, and the grain styles include vertical corrugation, horizontal corrugation, circular convex type, diamond convex type and other styles. The grain sample is determined according to the actual installation situation of the project and the aesthetic requirements of the appearance; the front glass 21 is treated with an acid etching process on the surface, which can increase the haze value of the glass surface and thus better hide the appearance contour of the crystalline silicon cell or the color difference of the cell edge and other problems, thereby improving the visual effect of the all-black appearance; the front glass 21 is finally treated with a double-layer coating process after acid etching. The double-layer coating can improve the weather resistance of the film layer while ensuring more light transmittance and appearance uniformity. The thickness of the double-layer coating is 210±20nm, the color difference of the reflected light in the 380-760nm band is small, the b value range is controlled in the range of -2 to 0, the surface roughness is controlled in the range of 0.3 to 1.2μm, and the overall appearance is uniform. At the same time, the transmittance curve of the double-coated glass is smooth, especially in the long-wave band (880nm-1100nm), the transmittance can be stably maintained at more than 94.0%, matching the spectral response curve of I BC high-efficiency batteries; it has the advantage of improving conversion efficiency.
[0057] In some embodiments, the front encapsulation film 22 is a transparent co-extruded EPE material 241. The transparent co-extruded EPE material 241 combines the good performance of POE film and the cost advantage of EVA film.
[0058] In some embodiments, the rear packaging film 24 includes a transparent co-extruded EPE material 241 and a black EVA material 242. By using the transparent co-extruded EPE material 241 and the black EVA material 242, low cost and a completely black appearance can be achieved at the same time.
[0059] The double-glass structure photovoltaic tile 20 of the present invention is an ultra-thick structure double-glass photovoltaic tile product, which has the advantages of low cost, anti-glare effect, full black appearance, and high conversion efficiency.
[0060] The following embodiments are for the manufacturing process of the double-glass structure photovoltaic tile 20 of 5mm rain pattern glass + EPE + back contact battery + EPE + EVA + 4mm float glass and the double-glass structure photovoltaic tile 20 of 4mm rain pattern glass + EPE + back contact battery + EPE + EVA + 4mm float glass.
[0061] Among them, the first preset time is 450s, the first preset temperature is 140℃; the first laminating board performs three-stage lamination on the first piece to be laminated: the first lamination is, the pressure value is -65kPa, and the pressurization holding time is 40s; the second lamination is, the pressure value is -55kPa, and the pressurization holding time is 40s; the third lamination is, the pressure value is -35kPa, and the pressurization holding time is 370s. The second preset time is 20s, and the second preset temperature is 150℃; the second laminating board performs three-stage lamination on the first piece to be laminated: the first lamination is, the pressure value is -60kPa, and the pressurization holding time is 40s; the second lamination is, the pressure value is -40kPa, and the pressurization holding time is 40s; the third lamination is, the pressure value is -30kPa, and the pressurization holding time is 800s.
[0062]
[0063]
[0064] Example 4 adopts the pressing method of this embodiment to manufacture double-glass structure photovoltaic tiles 20. The double-glass structure photovoltaic tiles 20 pressed out by the anti-overpressure frame 10 and the temperature-resistant pressure buffer pad have qualified appearance without bubbles, delamination, glass misalignment, battery parallel connection and other abnormalities. At the same time, the test results of key quality control items such as water boiling, peel strength, and cross-linking degree all meet the requirements. Example 1 is a method without using an overpressure-proof frame, a temperature-resistant pressure buffer and a lamination method. After lamination, the product has a certain proportion of bubbles, low crosslinking degree, low peel strength, water-boiling delamination failure and other abnormalities, which affect the lamination pass rate and product quality; based on the lamination parameters of Example 1, Example 2 is an example using an overpressure-proof anti-misalignment frame, and Example 3 is an example using a temperature-resistant pressure buffer; after comparison with Example 1, Example 2 and Example 3, the bubble defect ratio of Example 4 is reduced from 3.5% to 0%, the glass misalignment ratio is reduced from 1.5% to 0%, and the film edge thickness pass rate is increased from 97% to 100%; in terms of reliability, the reliability sampling pass rate of water boiling, wet freezing HF, etc. is increased from 90% to 100%. According to the results, the lamination pass rate, production cost advantage and reliability of the double-glass structure photovoltaic tile 20 are comprehensively improved.
[0065] It should be noted that the above exemplary numerical controls of temperature, time, pressure, etc. are only examples and do not limit the present invention.
[0066] This embodiment also provides a method for testing the thickness of the adhesive film of a double-glass photovoltaic tile, including the above-mentioned double-glass photovoltaic tile lamination method, and the testing method includes the following steps:
[0067] The second laminated member is laminated by the photovoltaic tile lamination method to obtain a test member, wherein the second laminated member comprises a front plate glass 21, an ETFE film, a front encapsulation film 22, a back contact cell 23, a rear encapsulation film 24, an ETFE film and a rear plate glass 25 arranged in sequence from top to bottom;
[0068] The front packaging film 22 and the rear packaging film 24 of the test piece are taken out to obtain a cross-linked combination after hot-melt cross-linking; the cross-linked combination includes the ETFE film, the front packaging film 22, the back contact battery 23, the rear packaging film 24 and the ETFE film;
[0069] The thickness of the four corners and the middle positions of the long and short sides of the cross-linked combination is measured respectively, that is, the thickness of the four corners, two thicknesses at the middle position of the long side, and two thicknesses at the middle position of the short side of the cross-linked combination need to be obtained, and the average thickness is calculated by these eight thicknesses;
[0070] The thickness average is compared to the theoretical value for the cross-linked combination.
[0071] The testing method of the present invention can be used to verify that the double-glass structure photovoltaic tile 20 obtained by the lamination method of the present invention is a qualified product that meets the requirements of the adhesive film retention rate and has no delamination risk.
[0072] Among them, ETFE film is used. After lamination, there is no adhesive force between the ETFE film and the front plate glass 21 and the rear plate glass 25. The front plate glass 21 and the rear plate glass 25 can be directly separated to obtain a cross-linked combination of the front plate film and the rear plate film; the front plate film and the rear plate film are cut into multiple blocks respectively, and the thickness of the multiple blocks is measured with a vernier caliper, and then the multiple measured thicknesses are averaged to obtain the measured value (i.e., the thickness average value) of the cross-linked combination of the front packaging film 22 and the rear packaging film 24.
[0073] It should be noted that, since the ETFE film is bonded to the adhesive film after lamination, the thickness of the ETFE film will affect the result when measuring the thickness of the adhesive film; therefore, further, the thickness of the ETFE film is 20 to 25 μm, so that on the basis of good isolation of ETFE, the accuracy of measuring the thickness of the adhesive film can be improved.
[0074] The theoretical value of the theoretical value of the cross-linked bond can be obtained by the following formula: (K / ρ)×A; A (retention coefficient) = 0.6-0.7, K is the weight of the film, and ρ is the density of the film.
[0075] According to actual verification, the average thickness of the film of the photovoltaic tile product with a weight of 430 grams + 360 grams + 360 grams is theoretically calculated to be 0.87 mm. At the same time, the average thickness of the film actually tested by the above method is 0.85 mm. The difference between the two is only 0.02 mm, which is within the error range of ±0.05 mm. This proves that the film thickness of the product obtained by lamination using the method of the present invention meets the standard and has good anti-delamination and anti-water vapor penetration properties.
[0076] In the description of the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "plurality" means two or more, unless otherwise clearly and specifically defined.
[0077] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A double-glass structure photovoltaic tile lamination method, wherein a first laminated component is sequentially laminated through a first lamination cavity and a second lamination cavity of a lamination device to obtain a double-glass structure photovoltaic tile (20), characterized in that: The first component to be laminated is arranged in an overpressure prevention frame (10) for lamination; The first lamination chamber is configured as follows: vacuuming for a first preset time, and the first lamination plate in the first lamination chamber performs segmented pressurization lamination on the first to-be-laminated component at a first preset temperature; The second lamination chamber is configured as follows: vacuuming is performed according to a second preset time, and the second lamination plate in the second lamination chamber performs segmented pressurization and lamination on the first component to be laminated according to a second preset temperature.
2. A double-glass structure photovoltaic tile lamination method according to claim 1, characterized in that: The overpressure prevention frame (10) has expansion and contraction in the X direction, and / or the overpressure prevention frame (10) has expansion and contraction in the Y direction.
3. A double-glass structure photovoltaic tile lamination method according to claim 2, characterized in that: The overpressure protection frame (10) comprises an L-shaped side (11), a long side (12) and a short side (13); both ends of the long side (12) and the short side (13) are provided with connection holes (14); both ends of the L-shaped side (11) are provided with connection parts (111) for connecting to the connection holes (14); the two long sides (12) are symmetrically arranged in parallel; the two short sides (13) are symmetrically arranged in parallel; the long sides (12) are perpendicular to the short sides (13); the long sides (12) and the short sides (13) are connected to form a rectangle through the L-shaped side (11); the connection parts (111) are slid in the connection holes (14) to achieve expansion and contraction, and are fixed by bolts (30).
4. A double-glass structure photovoltaic tile lamination method according to claim 3, characterized in that: The outer diameter of the connecting portion (111) is matched to the inner diameter of the connecting hole (14).
5. A double-glass photovoltaic tile lamination method according to any one of claims 1 to 4, characterized in that: The first laminating plate performs three-stage lamination on the first piece to be laminated, and the pressure values of the first, second and third stages of lamination increase successively; the first lamination, second and third stages of lamination are performed on the first piece to be laminated successively.
6. A double-glass structure photovoltaic tile lamination method according to claim 5, characterized in that: The second laminating plate performs three-stage lamination on the first laminated component, and the pressure values of the fourth, fifth and sixth stages of lamination increase successively; the first laminated component is sequentially laminarized in the fourth, fifth and sixth stages.
7. A double-glass structure photovoltaic tile lamination method according to claim 1, characterized in that: The first laminated component comprises a front plate glass (21), a front encapsulation film (22), a back contact battery (23), a rear encapsulation film (24) and a rear plate glass (25) which are arranged in sequence from top to bottom; the surface of the front plate glass (21) is provided with textures.
8. A double-glass structure photovoltaic tile lamination method according to claim 7, characterized in that: The laminating surfaces of the first laminate and the second laminate are both provided with buffer pads.
9. A double-glass photovoltaic tile lamination method according to any one of claims 7-8, characterized in that: The front packaging adhesive film (22) is a transparent co-extruded EPE material (241), and the rear packaging adhesive film (24) comprises a transparent co-extruded EPE material (241) and a black EVA material (242).
10. A method for testing the film thickness of a double-glass photovoltaic tile (20), characterized in that: A double-glass photovoltaic tile lamination method comprising any one of claims 1 to 6, A test piece is obtained by laminating a second piece to be laminated by the photovoltaic tile lamination method, wherein the second piece to be laminated comprises, arranged in order from top to bottom, a front plate glass (21), an ETFE film, a front encapsulation film (22), a back contact cell (23), a rear encapsulation film (24), an ETFE film and a rear plate glass (25); The front packaging film (22) and the rear packaging film (24) of the test piece are taken out to obtain a cross-linked combination after hot-melt cross-linking; the cross-linked combination comprises an ETFE film, a front packaging film (22), a back contact battery (23), a rear packaging film (24) and an ETFE film; The thickness of the four corners and the middle of the long and short sides of the cross-linked combination is measured respectively, and the average thickness is obtained by the thickness calculation; The thickness average is compared to the theoretical value for the cross-linked combination.
